Virtual Touch Quantification of the Salivary Glands for Diagnosis of Primary Sjögren Syndrome. (25th October 2016) - Chen, Shaoqi; Wang, Yukai; Chen, Shaoxing; Wu, Qiulin; Chen, Shigao
Abstract : Objectives: To investigate the value of salivary gland stiffness measured by Virtual Touch quantification (VTQ; Siemens Medical Solutions, Erlangen, Germany) for assessment of primary Sjögren syndrome. Methods: Fifty‐four patients with primary Sjögren syndrome, 35 patients without primary Sjögren syndrome (patients with dry mouth and dry eye symptoms), and 52 healthy control volunteers were included in this study. Patients with primary Sjögren syndrome were classified as early or advanced stage by labial gland biopsies. All participants underwent B‐mode sonography, on which the salivary glands (parotid and submandibular) were identified and VTQ measurements of shear wave velocity (SWV) were obtained. The diagnostic performance of SWV was evaluated by sensitivity and specificity at the optimum cutoff point and the area under the receiver operating characteristic curve. Results: For submandibular glands, the mean SWV ± SD values were 2.25 ± 0.34 m/s in patients with early‐stage primary Sjögren, 1.84 ± 0.20 m/s in patients without primary Sjögren syndrome, and 1.82 ± 0.27 m/s in healthy controls ( P < .001). With cutoff values of 2.15 and 2.10 m/s to separate patients with early‐stage primary Sjögren syndrome from those without Sjögren syndrome and healthy controls, the sensitivity and specificity were 77.1% and 85.4% and 79.2% and 83.9%, respectively. For parotid glands, the SWV values were 2.78 ± 0.82 m/s in patients with early‐stage primary Sjögren syndrome, 1.93 ± 0.33 m/s, in patients without primary Sjögren syndrome, and 1.85 ± 0.31 m/s in healthy controls ( P < .001). With cutoff values of 2.18 and 2.10 m/s to separate patients with early‐stage primary Sjögren syndrome from those without Sjögren syndrome and healthy controls, the sensitivity and specificity were 89.3 % and 75.3% and 91.4% and 80.0%. Conclusions: The VTQ technique might be a useful noninvasive strategy for assessment of salivary glands in the early stage of primary Sjögren syndrome.